Análise das políticas de valorização do Centro de Vitória-ES nas administrações de João Carlos Coser e Luciano Santos Rezende (2005-2020) - Vieira, Fabíola Candido Silva (2024)
The objective of this research is to investigate the revitalization policies of the Downtown area in the municipality of Vitória, State of Espírito Santo, carried out under the terms of office of João Carlos Coser and Luciano dos Santos Rezende, in the period from 2009 to 2020. We recognize that the region in study was the core of economic activities, which brings together central functions of political decisions, services and commercial exchanges. However, the promotion of various public policies encouraged displacement and an increase in population concentration in search of housing, generating the sprawl of the urban area. The strong appreciation of the beach region contributed to the production of urban space and the interest on the part of capital and real estate, stimulating the displacement of value production to other areas of the city, causing the abandonment of some buildings, transfer of the specific part of the municipal, state and federal administrative activities, structures and the desire on the part of civil construction and economic activities during the spatial restructuring of the city. We analyzed the actions promoted in other cities in Brazil and found that all of them had the aim of stimulating commercial exchange, making investments in housing and promoting incentives for tourism. We found that in the promises of governments, plans and projects that involved the theme of revitalization, of the two administrations developed, these issues were not developed to their fullest, they were not enough to reactivate the economy and/or improve the quality of life of the residents who already lived there, or, at least, stimulate the interest of new residents in the neighborhood. We noticed that the Downtown area did not present characteristics similar to those occurring in other Brazilian urban centers, such as increased prices of properties for sale, construction of new projects, retrofit renovations, demolitions of underused buildings and investments by businessmen in the construction. We recognize that the primary issue is valuing the lives of the people who live, work and enjoy the social space and that the settlement of the resident population is essential in maintaining the social structures of the environment and solidarity networks, in addition to developing rooting and feeling of belonging, promoting individual and social balance